Optimasi Proses Degradasi Metil Violet pada Reaktor Fotokatalitik Film TiO2-PEG - Ika Sri Sulfiana; Hardeli Hamzah; Irma Mon (Jurnal Periodic Jurusan Kimia UNP, 2012)
Methyl violet is one of triphenylmethane dyes which has been used extensively in various industrial application. Significant proportion of these dye enters the environment as wastewater. Photocatalytic degradation by using TiO2 under UV light irradiation has been shown to be potentially advantageous in the treatment of wastewater. This research was aimed to determine the optimum thin layers of catalyst and irradiation period of photocatalytic reactor. Modification by adding PEG was done to enhance TiO2 activity. A decrease in methyl violet concentration was analysed by using UV-Vis Spectrophotometer. GC-MS was used to ensure that there were a degradation indeed. Experimental results showed the optimum thin layers was reached in 8 times and  irradiation period was 5 hours. At this optimum condition, degradation percentage obtained was 79,03% with the initial concentration used was 10 mg/L and the flow rate was 110 mL/s. Identification by using GC-MS showed many peaks which proved there were degradation processes.